Sixth‐order differential Sallen‐and‐Key switched capacitor LPF using a‐IGZO TFTs. (23rd October 2018) - Wadhwa, Nishtha; Bahubalindruni, Pydi Ganga; Chapagai, Kamal; Goes, Joao; Deb, Sujay; Barquinha, Pedro
Summary: This paper presents sixth‐order fully differential active low pass RC and switched‐capacitor (SC) filters using N‐type IGZO thin‐film transistors for flexible wearable continuous health monitoring systems. As a first step, a low‐gain amplifier using a diode‐connected load and a fully differential amplifier is designed with positive feedback based on capacitor bootstrapping. These amplifiers present a gain around 5.03 and 40 dB, respectively, whereas their respective GBW product are around 450 and 200 kHz. Then these amplifiers are employed to realize biquads, with which a sixth‐order Sallen‐Key low‐pass RC and SC filters are implemented. The SC filter realized with low‐gain DDA has shown a simulated THD of −30.9 dB, SFDR of 30.1 dB, and a power consumption of 456 μW. On the other hand, the SC filter presents a THD of −31.4 dB, SFDR of 32.2 dB, and a power consumption of 573 μW with high‐gain differential difference amplifier (DDA) when a power supply of 10 V is used. Circuit simulations have been carried out in Cadence Virtuoso using in‐house IGZO TFT models. Abstract : This paper presents sixth‐order fully differential active low‐pass RC and switched‐capacitor (SC) filters using N‐type IGZO thin‐film transistors for flexible wearable continuous health monitoring systems. As a first step, a low‐gain amplifier using a diode‐connected load and a fully differential amplifier is designed with positive feedback based on capacitor bootstrapping. These amplifiers present a gain around 5.03 and 40 dB, respectively, whereas their respective GBW product are around 450 and 200 kHz. Then these amplifiers are employed to realize biquads, with which a sixth‐order Sallen‐Key low‐pass RC and SC filters are implemented. The SC filter realized with low‐gain differential difference amplifier (DDA) has shown a simulated THD of −30.9 dB, SFDR of 30.1 dB, and a power consumption of 456 μW. On the other hand, the SC filter presents a THD of −31.4 dB, SFDR of 32.2 dB, and a power consumption of 573 μW with high‐gain DDA when a power supply of 10 V is used. Circuit simulations have been carried out in Cadence Virtuoso using in‐house IGZO TFT models.